Analysis of the Effect of the Cooling System Modification on the Engine Performance of the Wuling Confero - Ullul Khairi; Risal Abu; Mukhnizar Mukhnizar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the effect of cooling system modification on the engine performance of the Wuling Confero vehicle. The main focus of this research is to evaluate the impact of thermostat removal and the use of plain water as a substitute for radiator coolant on engine operating temperature, engine speed (RPM), and fuel consumption. The research method used was a quantitative experimental approach, with direct testing using a Vehicle Diagnostic System (VDS) to obtain real-time data on operating temperature, RPM, and fuel consumption. The tests were conducted under three different conditions: the factory-standard cooling system (using a thermostat and coolant), the system without a thermostat, and the system using plain water. The results show that the factory-standard cooling system produced the most stable engine performance, with an optimal operating temperature of 80–92°C, stable RPM at around 750 ± 5, and the lowest fuel consumption of 3.8 ml/min. In contrast, the removal of the thermostat resulted in high temperature fluctuations (±6–8°C), unstable engine speed reaching up to 825 RPM, and the highest fuel consumption at 5.2 ml/min. Meanwhile, the use of plain water showed no statistically significant difference but caused moderate temperature fluctuations (±4.3°C) and a higher risk of long-term corrosion. The Wilcoxon statistical test indicated significant differences between the standard and thermostat-removed systems (Z = −2.81; p < 0.05), as well as between the thermostat-removed and plain-water systems (Z = −2.14; p < 0.05). Cooling system modification particularly by removing the thermostat has a negative impact on temperature stability and engine thermal efficiency. The factory-standard cooling system remains the most efficient configuration and is strongly recommended to maintain optimal performance, fuel efficiency, and engine durability.